Globalization and Deindustrialization: Direct lnvestment and the Decline of Manufacturing Employment in 17 OECD Nations - Arthur S. Aldersen (Journal of World-Systems Research, 2015)
Recent years have witnessed a fairly dramatic upswing in the level of foreign direct investment, a phenomenon which has played an integral part in a larger process of globalization. While sociologists have devoted a good deal of attention to the consequences of direct investment for the developing hosts of foreign direct investment, much less attention has been paid to the implications of direct investment for the advanced industrial societies. ln this paper, I focus on one of the more interesting links that has been drawn between direct investment and its effects: that between the outflowof direct investment - often cast as "capital flight" - and deindustrialization. To examine this link I employ a pooled time-series of cross-sections dataset which combines observations on 17 OECD nations across the 1967-1990 period (N=408) . Random effects regression models, which control for unmeasured country-specific effects, reveal strong support for arguments which link direct investment to the relative decline of the labor force in manufacturing in core societies. ln addition, results show that deindustriali zation across this period is largely explained by a model that combines classic generalizations of the process of economic development with an attention to a range of more immediate factors identified by contemporary students of deindustrialization.